Seeing Like a Tesla: How Can We Anticipate Self-Driving Worlds? (Glocalism: Journal of Culture, Politics and Innovation, 2017)
In the last five years, investment and innovation in self-driving cars has accelerated dramatically. Automotive autonomy, once seen as impossible, is now sold as inevitable. Much of the governance discussion has centred on risk: will the cars be safer than their human-controlled counterparts? As with conventional cars, harder long-term questions relate to the future worlds that self-driving technologies might enable or even demand. The vision of an autonomous vehicle – able to navigate the world’s complexity using only its sensors and processors – on offer from companies like Tesla is intentionally misleading. So-called “autonomous” vehicles will depend upon webs of social and technical connectivity. For their purported benefits to be realised, infrastructures that were designed around humans will need to be upgraded in order to become machine-readable. It is vital to anticipate the politics of self-driving worlds in order to avoid exacerbating the inequalities that have emerged around conventional cars. Rather than being dazzled by the Tesla view, policymakers should start seeing like a city, from multiple perspectives. Good governance for self-driving cars means democratising experimentation and creating genuine collaboration between companies and local governments.
Keywords: Tesla; self-driving cars; automotive autonomy; risk, governance